2014
DOI: 10.1002/ana.24162
|View full text |Cite
|
Sign up to set email alerts
|

Cortical interneuron loss and symptom heterogeneity in Huntington disease

Abstract: These findings suggest that region-specific degeneration of cortical interneurons is a key component in understanding the neural basis of symptom heterogeneity in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…Staining by IHC is similarly eliminated in the cerebellum (Airaksinen et al, ). Labeling of calbindin is consistent with previous reports (Kim et al, ). Calretinin (Swant, cat no. CG1, RRID:AB_10000342).…”
Section: Methodssupporting
confidence: 93%
“…Staining by IHC is similarly eliminated in the cerebellum (Airaksinen et al, ). Labeling of calbindin is consistent with previous reports (Kim et al, ). Calretinin (Swant, cat no. CG1, RRID:AB_10000342).…”
Section: Methodssupporting
confidence: 93%
“…Different studies have shown the involvement of multiple striatal cell types (MSNs, GINs, oligodendrocytes, and astrocytes) in addition to other cardinal brain regions and cell types in HD (34)(35)(36)(37). All of these cellular subtypes are elaborated in a regionaland temporal-specific manner during neural development.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the PREDICT-HD and the Huntington Study Group investigations have shown that white matter abnormalities are one of the best predictors of diagnostic proximity to HD (Paulsen et al, 2010), and also correlates with cognitive impairment in pre-manifest cases of HD (Beglinger et al, 2005). On the other hand, selective changes in the complement of interneurons in primary motor cortex and cingulate cortex are strongly linked to symptom heterogeneity in HD, particularly with respect to motoric and mood disorders (Kim et al, 2014). Additional studies have also shown important cognitive correlates with volumetric changes in the nucleus accumbens and the thalamus during the prodromal phase of disease (Aylward et al, 2013).…”
Section: Introductionmentioning
confidence: 99%